Pengaruh Dukungan Sosial Orang Tua dan Metode Pengajaran Terhadap Motivasi Belajar Renang Pada Siswa Usia Dini - Atikawati Fhadillah; Januar Abdilah Santoso (Jurnal Porkes, 2026)
Background: Learning motivation in early childhood swimming is crucial for success in aquatic education. Parental social support and appropriate teaching methods are hypothesized to significantly enhance learning motivation. Objective: This study examines the influence of parental social support and teaching methods on swimming learning motivation in early childhood students. Methods: A quantitative correlational design was employed. The sample comprised 25 children aged 4–6 years from Gemilang Swimming Club, Samarinda, selected through total sampling. Instruments included Likert-scale questionnaires for parental social support (14 items), teaching methods (21 items), and swimming learning motivation (15 items, administered via child-friendly interviews). Data were analyzed using multiple regression with SPSS 26.0. Results: Parental social support significantly influenced learning motivation (β = 0.212, t = 2.629, p = 0.015). Teaching methods significantly influenced learning motivation (β = 0.783, t = 9.714, p < 0.001). Together, both variables significantly predicted learning motivation (F = 37.682, p < 0.001), explaining 77.4% of the variance (R² = 0.774). Conclusion: Both parental social support and teaching methods significantly enhance swimming learning motivation in early childhood, with teaching methods having a stronger effect.